Photoelectric peculiarities of electric photographic and holographic recording media with ionic dyes - Davidenko, N.A.; Ishchenko, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The features of formation and relaxation of metastable connected states of cation-radical of carbazole and negatively charged fragment of dye molecule were investigated in the films of poly-N-epoxypropilcarbazole doped with intraionic and cation dyes. In films with intraionic dye these states collapse at irradiation with light from the range of dye absorption, and in films with cation dye such states do not collapse under light action. Observed peculiarities are caused by structure features of the dyes.